Decomposing service exports adjustments along the intensive and extensive margin at the firm-level - Elisabeth Christen; Michael Pfaffermayr; Yvonne Wolfmayr (Austrian Institute of Economic Research (WIFO), 2017)
Using a panel-data set of Austrian service exporting firms this paper examines the determinants of service exports at the firm-destination country level. We implement a random-effects Heckman sample selection firm-level gravity model as well as a fixed effects Poisson model. Expected firm-level service exports are decomposed into the intensive and extensive margins of adjustment as a response to counterfactual changes. We find market demand to be the key determinant. Results also suggest high service export potentials due to regulatory reform in partner countries within the EU. Adjustments at the extensive margin only play a marginal role. Increasing firm size as well as changes in distance related costs are most effective in developing new export relationships in services.
Keywords: C15; C21; D21; F14; L20; L80; 330; Services trade; Firm-level evidence; Firm heterogeneity; Gravity model; Sample selection; Intensive and extensive margin of trade